NIR‐II Responsive Hydrogel as an Angiogenesis Inhibition Agent for Tumor Microenvironment Reprogramming. Issue 47 (24th September 2021) - Zhao, Senfeng; Zhang, Ling; Deng, Liu; Ouyang, Jiang; Xu, Qianqian; Gao, Xinyu; Zeng, Zhilin; Liu, You‐Nian
Abstract: Regulation of angiogenesis is a great challenge for effective anticancer therapy. Generally, anti‐angiogenic therapies are focused on inhibition of inducers involved in pro‐angiogenic communication pathways. Despite the great potential of anti‐angiogenic therapy, engineering efficient angiogenesis inhibition agents (AIAs) is still a formidable challenge, since most anti‐angiogenic therapies are limited due to the cancer recurrence via compensatory expression of different angiogenic mediators. Herein, we present a new strategy of near‐infrared‐II (NIR‐II) responsive hydrogel AIAs, constructed by incorporation of nitric oxide (NO) precursor (BNN6) and 2D WO2.9 nanosheets within hydrogel (WB@hydrogel). Because of the defect/2D engineering, the bandgap of the WO2.9 nanosheets narrows, which extends the absorption to the NIR‐II region. It offers a favorable NIR‐II controlled manner for NO generation through irradiation time and light intensity. The continuous supply of NO can activate the expression of wild‐type p53 protein and further reverse the transcriptional expression of pro‐ and anti‐angiogenic factors of the tumor microenvironment (TME), subsequently alternating pro‐angiogenic TME to anti‐angiogenic TME. In the murine tumor model, this method achieved high tumor growth inhibition (TGI) rate and excellent anti‐recurrence efficiency. Abstract : NO‐precursor BNN6 and WO2.9 nanosheets are uniformly encapsulated into agarose hydrogel. WO2.9 induced by hydrogenation reaction from WO3 offer NIR‐II inertia hydrogel ability of NIR‐II response. With the controllable release of NO under NIR‐II laser irradiation, NO penetrates into deep tumor interiority and reprograms the tumor pro‐angiogenetic environment, achieving effective vessels eradication in tumor sites.